The Influence of Brand Personality, Service Quality, and Store Atmosphere toward Repurchase Intention Ethic Barbershop Padang - Muhammad Nuzul Ragil Fadillah; Thamrin Thamrin (Jurnal Kajian Manajemen dan Wirausaha, 2019)
The purpose of this research are to analyze : (1) The effect of entrepreneurial motivation on entrepreneurial intention public university student’s in Padang (2) The effect of family environment on entrepreneurial intention public university student’s in Padang. The type of this research is causative research. The population on this research is all of  public university student’s in padang . The total sample of this research was 150 persons with online survey. The result of research shows that (1) Entrepreneurial Motivation has significant effect on Entrepreneurial Intention Public University Student’s in Padang (2) Family Environment has significant effect on Entrepreneurial Intention Public University Students in Padang. Entrepreneurial motivation and family environment have significant effect on entrepreneurial intention. For the future research is better to explore more about variable that can influence entrepreneurial intention.Keywords: Entrepreneurial Motivation, Family Environment and Entrepreneurial Intention